Catalytic pyrolysis of crofton weed: Comparison of their pyrolysis product and preliminary economic analysis. Issue 2 (23rd August 2021) - Lin, Jin; Cheng, Song
Abstract: Pyrolysis of crofton weed with or without catalyst is investigated in a microwave furnace to determine the effect of ZnO and Na2 CO3 catalyst on the yields and properties of pyrolysis products. The ZnO and Na2 CO3 are found to increase the yield of bio‐oil and decrease the content of carboxylic acid in bio‐oil. The result shows that catalytic pyrolysis can improve the quality of bio‐oil. The bio‐gas produced from catalytic pyrolysis has larger content of CO and less CO2 as compared to non‐catalytic pyrolysis, particularly for ZnO catalyst pyrolysis process. ZnO and Na2 CO3 improve the pore structure of bio‐char in the catalytic pyrolysis process. Bio‐char produced from ZnO catalytic pyrolysis could be used as photocatalyst to degrade dye wastewater. Besides, catalytic pyrolysis system is profitable, based on preliminary economic analysis. Our findings provide a successful example of crofton weed converting into three useful pyrolysis product, which is worthy of further study.